2015
DOI: 10.1093/hmg/ddv124
|View full text |Cite
|
Sign up to set email alerts
|

Impact of age, BMI and HbA1c levels on the genome-wide DNA methylation and mRNA expression patterns in human adipose tissue and identification of epigenetic biomarkers in blood

Abstract: Increased age, BMI and HbA1c levels are risk factors for several non-communicable diseases. However, the impact of these factors on the genome-wide DNA methylation pattern in human adipose tissue remains unknown. We analyzed the DNA methylation of ∼480 000 sites in human adipose tissue from 96 males and 94 females and related methylation to age, BMI and HbA1c. We also compared epigenetic signatures in adipose tissue and blood. Age was significantly associated with both altered DNA methylation and expression of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
234
5
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 191 publications
(267 citation statements)
references
References 90 publications
25
234
5
3
Order By: Relevance
“…However, after correction for multiple testing, Arner and colleagues were unable to find significant associations between the investigated methylation sites and insulin resistance in this cohort. Nevertheless, they present thousands of differentially methylated sites based on a nominal association, and validate their results by showing that some of them are also found in similar studies of DNA methylation in adipose tissue related to BMI, type 2 diabetes or weight loss [6,[9][10][11]. For example, 591 differentially methylated sites identified in adipose tissue of individuals with type 2 diabetes compared with nondiabetic controls in a study by Nilsson et al were also found to be nominally associated with insulin resistance in the study by Arner et al [6,9].…”
Section: Dnmt Dna (Cytosine-5)-methyltransferase Pbmc Peripheral Bloosupporting
confidence: 61%
See 1 more Smart Citation
“…However, after correction for multiple testing, Arner and colleagues were unable to find significant associations between the investigated methylation sites and insulin resistance in this cohort. Nevertheless, they present thousands of differentially methylated sites based on a nominal association, and validate their results by showing that some of them are also found in similar studies of DNA methylation in adipose tissue related to BMI, type 2 diabetes or weight loss [6,[9][10][11]. For example, 591 differentially methylated sites identified in adipose tissue of individuals with type 2 diabetes compared with nondiabetic controls in a study by Nilsson et al were also found to be nominally associated with insulin resistance in the study by Arner et al [6,9].…”
Section: Dnmt Dna (Cytosine-5)-methyltransferase Pbmc Peripheral Bloosupporting
confidence: 61%
“…As previous studies have linked adipose tissue DNA methylation to both BMI and type 2 diabetes [8][9][10], it is reasonable to assume an association also with insulin resistance. However, after correction for multiple testing, Arner and colleagues were unable to find significant associations between the investigated methylation sites and insulin resistance in this cohort.…”
Section: Dnmt Dna (Cytosine-5)-methyltransferase Pbmc Peripheral Bloomentioning
confidence: 96%
“…In addition, changes in cell type composition could be responsible for some of the changes in HFO-induced gene expression. However, when we investigated 24 cell-typespecific markers for adipocytes, pre-adipocytes, brown adipocytes, macrophages, cytokines and inflammation [12], only LEP, TNF (cytokines) and CIDEA (brown adipocyte marker) were differentially expressed after HFO. These data suggest that 5 days HFO does not alter the cellular composition of SAT.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, young, healthy LBW men develop more severe peripheral insulin resistance when exposed to 5 days of high-fat overfeeding (HFO) compared with men with a normal birthweight (NBW) [1]. Lifestyle-related factors may alter epigenetic and transcriptional patterns [5][6][7][8][9][10][11][12], and thereby affect the risk of metabolic diseases. Indeed, we observed widespread DNA methylation changes in skeletal muscle from healthy young men after 5 days of HFO [7]; in contrast, there were no significant epigenetic changes in matched LBW men after HFO [13].…”
Section: Introductionmentioning
confidence: 99%
“…This may be due to the facts that environmental factors (including nutrition) across individuals are very heterogeneous, and target tissues (such as adipose tissue) are not easy to access. Furthermore, recent data by Rönn et al suggests that the human DNA methylome in SAT changes considerably with age [185]. They also found BMI exerts effects on the degree of DNA methylation in human adipose tissue, proposing that obesity can mediate some of its effect through changes in the epigenome.…”
Section: Epigeneticsmentioning
confidence: 96%